One-Way Delay and Goodput Measurements with a VDSL, DOCSIS, and MPTCP Internet Access - Ammon, Lorenz; Deutschmann, Jörg; Hielscher, Kai-Steffen; German, Reinhard (2020 43rd International Conference on Telecommunications and Signal Processing, TSP 2020, 2020)
Different Internet access technologies have both advantages and disadvantages. Two common wire-based standards are Very high speed Digital Subscriber Line (VDSL) and Data Over Cable Service Interface Specification (DOCSIS). The simultaneous use of multiple Internet access links can be achieved with Multipath TCP (MPTCP). This paper presents one-way delay and bulk data transfer measurements of a typical end-user DSL as well as DOCSIS Internet access. In addition, MPTCP is used for bandwidth aggregation of both Internet access links. The results show that the DSL Internet access has a more stable performance than the DOCSIS Internet access. MPTCP can provide bandwidth aggregation unless the link rates are too different. The observed fluctuations indicate that Internet access link models with simple impairment assumptions need to be extended. However, some effects cannot be explained without having access to the operator and backbone infrastructure.
CRIS-Team Scopus Importer:2020-09-18
Keywords: DOCSIS; Goodput; Hybrid Access; Multipath TCP; Network Measurements; One-Way Delay; Throughput; VDSL